Dissertações Unesp 2015 Nota 4: Um Estudo Da Coesão E Coerência - Battaiola, Viviane Segatto [UNIFESP] (2017)
The aim of this research is to study the aspects of cohesion and coherence of the grade 4dissertations’of theentrance examination of the São Paulo State University in 2015, under the theoretical perspective of Textual Linguistics with such aspects supported, respectively, in the studies of the Brazilian author Ingedore Villaça Koch (2009, 2013, 2015) and in the studies of the French author Michael Charolles (1988). It was tried to not completely separate the concepts by authors, since both go through both textual mechanisms. From the Koch readings and the author Luiz Antônio Marcuschi (2008, 2012), the socio-cognitive-interactionist phase of LT was located temporally in the late 1980s and early 1990s, in which it was tried to insert our study to understand the use of language as a historically situated cognitive-based social activity. From this point of view, the text is considered an "unit of use or communicative" (MARCUSCHI, 2012, p.22). As the text is a fruit of the socio-historical context in which it isinserted, the entrance examination and the correction criteria of the dissertations established by the 2015 Applicants Handbook were contextualized, explaining the operation of the selection process through the information channels of the 2015 Applicants Handbook. Bakhtin (1979, 2006) was studied to understand the concept of secondary discursive genre, in which the dissertation of theentrance examination is located and a dissertation grade 10 that corresponds to the expectations of the correction criteria was analysed. The work was developed with the intention of understanding the writing problems found in the texts written from the unique theme defined by the entrance examination test: The legacy of slavery and prejudice against black people in Brazil. The wording of the essay test guided the candidate to make use of the 4 texts presented in the writing exercise that served as the basis for writing, as well as other texts known by the candidate. In this dialogical language relationshipa Bakhtinian concept we use to define the relation between reading and writingthe cohesive elements of dissertations grade 4were analyzed, and we noticed that the informativeness of the text harms this relation, since the arguments are insufficient to consistently support the theme to be defined. In this way, taking Charolles's principles of coherence into consideration,"it leads to postulating that there are no sequences of incoherent statements in themselves, since in an interaction it is always possible to construct a context in which a seemingly incoherent sequence becomes meaningful" (KOCH, 2009, p.20), it was shown that the lack of informativeness in grade 4 dissertations does not present elements of specific recurrence throughout its reading, that is, "repetition"; by its "progression", the second condition that makes the text coherent from the necessity of having in it an increase of contents are left to arguments already known; and, therefore, the "relation" between the words does not lead us to consistent arguments either.